2015
DOI: 10.3233/rnn-150507
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized clinical trial on the efficacy of magnetic sacral root stimulation for the treatment of Monosymptomatic Nocturnal Enuresis

Abstract: Purpose: Purpose of this study was to evaluate the long term efficacy of repetitive sacral root magnetic stimulation (rSMS) in patients with monosymptomatic nocturnal enuresis (MNE). Methods: Forty four patients were randomized to receive either sham or real repetitive sacral root magnetic stimulation (rSMS; 15 Hz with a total of 1500 pulses/session) for 10 sessions. Evaluation was performed before starting treatment, immediately after the 5th and 10th treatment session, and 1 month later, using frequency of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…Yamanishi et al compared MS with FES, Fergany et al compared MS with TENS, and remaining studies compared MS with sham. One study did not document the treatment of sham device, two studies used the 20.4% of active stimulation, two studies utilized the sham stimulating coil as the experimental group, one study applied 1 Hz as the sham stimulation, one study performed the sham stimulation with a thin deflective aluminium plate inserted in the chair, and remaining studies adopted stimulation with inactive device as the experimental group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yamanishi et al compared MS with FES, Fergany et al compared MS with TENS, and remaining studies compared MS with sham. One study did not document the treatment of sham device, two studies used the 20.4% of active stimulation, two studies utilized the sham stimulating coil as the experimental group, one study applied 1 Hz as the sham stimulation, one study performed the sham stimulation with a thin deflective aluminium plate inserted in the chair, and remaining studies adopted stimulation with inactive device as the experimental group.…”
Section: Resultsmentioning
confidence: 99%
“…But et al found active MS treatment had significant improvement in number of leaks and bladder volume at strong desire to void ( P = 0.07, P = 0.022, respectively) with 2 month duration; with no change between the two groups in bladder capacity at first desire to void ( P = 0.059). One study by Khedr at al showed that there was a significant difference between the MS therapy and sham group in number of leaks, QOL, and VAS score, with a P ‐value of 0.001.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• подавлению обратного нейронального захвата норадреналина и серотонина [45]; • стимуляции афферентных волокон пудендаль-ного нерва в составе крестцовых корешков [46]; • активации спинальной опиодной системы, подавляющей сокращения детрузора [47]; • стимуляции эфферентных волокон тазового нерва в составе крестцовых корешков [48]. В исследовании P. M. Braun и соавт.…”
Section: Sacral Micturition Centerunclassified